Managing Young Human Resource Behaviors through Character Education - Asad Asad; Fridiyanto Fridiyanto (Universitas Jambi, Indonesia, 2020)
The purpose of this research was to explore what efforts were being made by the Madrasah Tsanawiyah Bungo Regency in order to foster and embed character education in their students, in particular; how to plan, implement, supervise, and evaluate character education for students in One State Madrasah Tsanawiyah Bungo Regency. This research was a qualitative research with a case study approach. In collecting the data, the researcher used a demographic background and an in-depth interview with 9 participants. The participants in this research were one principal, two vice principals, three teachers, and three students. Based on the findings of the research, it concluded the design of this education plan had been carried out periodically from the beginning of the year by perfecting the plan of the previous year and continued by making a plan for the following year which was carried out by a deliberation meeting with the teacher assembly and entered into the education calendar. The finding related to the implementation of character education was carried out by integrating character education into daily activities at the madrasah and building communication between schools with parents of students. Furthermore, the finding of supervision showed that each party in the school such as the principal, vice-principals and teachers played an active role in supervising both directly and indirectly. The teacher was the party that had an active role because the teacher in addition to overseeing student actions, teacher also taught about how to inculcate character education in the classroom so that it can improve student behaviors by giving a warning. In terms of evaluation, it showed that the learning process of character education had been going quite well and in accordance with what was expected even though there were still shortcomings such as there were teachers who still did not understand the materials well, so the learning process was still less interesting and satisfying, especially in religious learning.